Decolonizing Nepal’s Kiranti-Kõits grammar and lexicon - Rapacha, Lal-Shyãkarelu (Journal of Nepalese Studies, 2024)
This article proposes to explore how indigenous languages are colonized in terms of grammar and lexicon in daily usage whether in spoken or written forms by the speakers of Kiranti-Kõits कराँती-कोँइच , who were socio-psychologically and politically over-dominated by the imposed official language of the ruler-colonizers during the periods of internal colonization or invasion of the present-day eastern Nepal first by Shah Regime after AD1768 and later continued by Ranarchism for 104 years till AD1950 in the past-atrocious-history of Nepal. Due to such adverse socio-political situations following the loss of Indigenous Kirant’s (also spelt as ‘Kirat’ historically developed from ‘Oirat’) sovereign land territory, the Kiranti nations’ (sovereign peoples) languages were either pidginized or creolized (commonly as hybridization) by the colonizer’s privileged Khas-Nepali language in such a way that those languages in the near future will lose their organic linguistic structures along with lexicon of Kiranti-ness as for instance the Kiranti-Kõits is one of them. Thus, this article aims to reverse this grammatical colonization or linguistic imperialism by rediscovering, reviving, regaining, and reinterpreting or reestablishing those disappeared features of auxiliaries, phonemes, and indigenize or even re-indigenize such organic Kiranti- Kõits linguistic features and sovereignty of its own through decolonization or indigenization process as our giant neighbouring country—India’s, such as Kolkata from Calcutta, Mumbai from Bombay, Chennai from Madras. Scholars, researchers, writers, and higher education’s academia have already been doing so for decolonizing the colonized loconyms etc. and more importantly in 1989 Myanmar has decolonized itself from Burma.